Agent-based simulation of labour mobility and relocation choices - Lizner, Pavel; Zouhar, Jan, 1982-; Dvořák, Marek; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
Agent-based simulation is a topic Thomas Schelling became famous for. My work is derived from his ideas and from the principals of cellular automata . However, my aim is to simulate relocation of people depending on their current job and jobs which they can relocate to - in MatLab. Main factors affecting their decision are social interactions and social services which are offered on the given positions and which are looked upon differently with the person's age. The goal of the work is monitor the changes in outcomes when different parameters and conditions are set. Will people change their jobs at all with one setting or on the contrary will there be an infinite loop of people looking for better position?
Vedoucí práce: Jan Zouhar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses